Finding the cost of control - Judd Kessler; Stephen G. Leider (Center for Economic Studies and ifo Institute (CESifo), 2013)
A large and growing literature has demonstrated that explicit incentives, such as enforceable contracts, can lead agents to withhold effort. We investigate when this behavioral result arises. In an extensive laboratory experiment, we find that imposing control through an enforceable contract is only detrimental to principals in a special case when: (1) there is a preexisting norm that agents provide high effort; (2) control is imposed unilaterally and has an asymmetric effect on the agent; (3) control is weak (i.e. it cannot induce significant effort); and (4) the agent does not use control when acting as a principal.
Keywords: C90; J30; L20; 330; experiment; principal-agent problem; hidden cost of control